2003
DOI: 10.1002/bem.10117
|View full text |Cite
|
Sign up to set email alerts
|

Ocular effects of radiofrequency energy

Abstract: Radiofrequency (RF) energy has been reported to cause a variety of ocular effects, primarily cataracts but also effects on the retina, cornea, and other ocular systems. Cataracts have been observed in experimental animals when one eye was exposed to a localized, very high RF field and the other eye was the unexposed control. The results show that 2450 MHz exposures for >or=30 min at power densities causing extremely high dose rates (>or=150 W/kg) and temperatures (>or=41 degrees C) in or near the lens caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 51 publications
2
64
0
Order By: Relevance
“…Based on studies by his group, he concluded that temperatures exceeding 41 C would be required to produce cataracts in the rabbit eye. The present writer notes that this concurs with Elder's conclusion that microwave exposures could produce cataracts in the rabbit, but only at high exposures sufficient to heat the lens to temperatures greater than or equal to 41 C [5]. However, this present writer notes, the issue remains controversial, given the existence of a scattering of literature, mostly involving experiments on cultured lenses, reporting that somewhat lower microwave exposures can induce opacities in lens tissue [13].…”
Section: Ocular Effectssupporting
confidence: 77%
See 1 more Smart Citation
“…Based on studies by his group, he concluded that temperatures exceeding 41 C would be required to produce cataracts in the rabbit eye. The present writer notes that this concurs with Elder's conclusion that microwave exposures could produce cataracts in the rabbit, but only at high exposures sufficient to heat the lens to temperatures greater than or equal to 41 C [5]. However, this present writer notes, the issue remains controversial, given the existence of a scattering of literature, mostly involving experiments on cultured lenses, reporting that somewhat lower microwave exposures can induce opacities in lens tissue [13].…”
Section: Ocular Effectssupporting
confidence: 77%
“…As used in these studies, 'behavioural disruption' refers to the change in behaviour of an animal from an assigned task. This could be either work stoppage or switching to a thermoregulatory behaviour, such as in rats spreading saliva on the tail, a behaviour observed in this species when in warm By contrast, the limits in both the IEEE standard and ICNIRP for partial-body exposure were set on the basis of data showing injury (cataracts) in rabbits at exposure levels above 100 W/kg to the eye, causing local tissue temperatures to increase above 41.5 C in or near the lens [5]. After incorporation of a suitable safety factor, this led to limits for partial body of exposure of 2 and 10 W/kg for the general public and occupational exposures, respectively, averaged over 10 g of tissue.…”
Section: Thermal Basis Of Two Major Exposure Standardsmentioning
confidence: 99%
“…The possibility of adverse effects (e. g. cataracts in the lenses) was investigated in several studies. Although, adverse ocular effects were only found for SAR values well above values that occur in the eye from the use of mobile phones [22], there remains some concern about possible adverse health effects from high peak-power, pulsed microwave radiation [93]. Current results, however, support the conclusion that clinically significant ocular effects do not occur for low-level microwave radiation [22].…”
Section: Ocular Effectsmentioning
confidence: 91%
“…This study did not find an increased risk. Overall, there is no clear evidence of an association between mobile phone radiation and ocular cancer [22].…”
Section: Cohort Studiesmentioning
confidence: 97%
“…Lin [14] reviewed the possibility of cataract formation and showed that the temperature increases were too small to cause cataracts under normal conditions. The Stewart Report [15] includes a brief summary of experimental studies into RF effects on the eye and Elder produced a more detailed analysis [16]. They reported that pulsed RF fields at 2.45GHz, at moderate SAR levels, produced harmful effects in primates including lesions in the corneal endothelium and increased vascular leakage from the blood vessels of the iris.…”
Section: Introductionmentioning
confidence: 99%